Analysis of The Level of Knowledge of Adolescents About Whiteness In Madrasah Aliyah Negeri 2 Samarinda - Rahayu, Anik Puji (Mulawarman Nursing Indonesia Journal, 2024)
ABSTRACT Introduction: Vaginal discharge is secretion that appears from the vaginal canal without bleeding. Vaginal discharge can occur both physiologically (normal) and pathologically (abnormal) (Gampu et al., 2018). The aim of this research is to describe the knowledge of young women about vaginal discharge among female students at MAN 2 Samarinda. Methodology: This research uses descriptive quantitative research. The sample in this research was 51 respondents, with a total sampling technique. Research Results: From 51 respondents studied, 39 were obtained respondents or (76.5%) respondents Which own level knowledge tall, respondents with moderate knowledge were 10 respondents or (19.6%) and respondents with knowledge low in get 2 respondents or (3.9%) respondents. Conclusion: Based on the results of research conducted on 51 respondents, although the level of knowledge about vaginal discharge is high, namely 76.5%, it is still necessary to provide knowledge about vaginal discharge and carry out re-research on vulva hygiene and preventing recurrent vaginal discharge in adolescents. Keywords: Knowledge, Young Women, Vaginal Discharge